Financial Performance of Banks in Bancassurance: A Study with Special Reference to State Bank of India - C. H., Sreesha; Joseph, M. A. (Indian Journal of Finance, 2011)
One of the most significant changes in the financial service sector over the past few years has been the growth and development of bancassurance. In present scenario, Banking institutions and insurance companies have found bancassurance to be an attractive and profitable compliment to their existing activities. This research study endeavors to diagnose some realities behind bancassurance business of State Bank of India. To judge the financial viability of the bank in bancassurance, the CAMEL Model, which is the approved model of Reserve Bank of India has been used. The reason behind the use of the CAMEL model is that it measures the performance of bancassurance in almost all the variables.